Electro-mechanical impedance technique for concrete strength monitoring: Three-dimensional model development and experimental verification - Ma, Yongli; Meng, Xiaoyu; Yao, Chi; Zhang, Xiaobo; Dong, Wanjing; Li, Yingwei; Jiang, Qinghui; Zhou, Chuangbing (Measurement : journal of the International Measurement Confederation, 2023)
•A three-dimensional EMI model for the embedded piezoelectric sensor is developed.•The hardening process of concrete is measured by the PS-EMI and CPS-EMI thchnique.•The contradiction in the trend of conductance spectrum is observed.•The underlying mechanism that induce the conductance spectrum difference is discussed. During the application of the electro-mechanical impedance (EMI) technique for detecting the strength development of concrete, in some cases, the piezoelectric sensor is embedded in the concrete. Normally, there are two methods to embed the piezoelectric sensor: PS-EMI and CPS-EMI. For both methods, the observed resonance frequency of the piezoelectric sensor increases with the increase of the concrete strength. However, there is a contradiction in the trend of conductance amplitude at the resonance frequency, which has to an extent puzzled the researchers in this area. In this paper, we developed a three-dimensional EMI model for the embedded piezoelectric sensor. We discussed the underlying mechanism, which induces the conductance spectrum difference for the PS-EMI and CPS-EMI, and experimental verification was carried out. By plotting the evolution of the concrete strength as a function of the resonance frequency shift, it was found that both embedding methods can be used in practical applications.